Superação de dormência de sementes e crescimento inicial de plântulas de umbuzeiro - Campos de Melo, Aniela Pilar (2012)
Pre-germination treatments such as scarification and the use of growth regulators can provide the overcoming of dormancy in seeds and enhance the emergence and development of seedlings. The aim of this study was to determine appropriate treatments to overcoming seed dormancy and enhance the initial growth of seedlings of Spondias tuberosa. We used a randomized design in factorial 2 x 4, with the following factors: seeds scarified or not scarified and then soaked in water or aqueous solutions of gibberellin, cytokinin and ethylene, with 4 replicates and 15 seeds. There was no significant interaction between scarification treatments and use of growth regulators. Mechanical scarification and soaking of seed of umbuzeiro in solutions containing growth regulators does not increase the percentage of seedling emergence, however soaking in a solution of Ethrel at 100 ppm provides higher speed of emergence and root development.